Data transmission using aes encryption via email and sms - Arif Hanafi, Sharif Katullah (2013)
A computer, and other mobile computing devices, are generally accepted globally as a personal computing platform. Given the amount of sensitive information gathered by these devices, there are serious privacy and security implications for both individual use and enterprise organization. Confidentiality of the data can be effectively restricted by deploying an encryption file technique. All major computers Operating System now integrates some form of encryption. In certain situations, this is inadequate, as users may be forced into disclosing their decryption keys. In this case, the data must be hidden so that it is very certainly transmit sensitive information but unable to intercept easily if not encrypt before sending to the intended person. Encryption and decryption technique while the interior structure's strength of the data file depends on the key/password it used. This thesis priority is to avoid the using of the manual process such as hand-to-hand method transmission while maintaining the concealment of their sensitive or confidential data and explores the usefulness of encryption for computer devices. Users especially choose weak technique. The goal is to ensure the confidential data is not reachable for unauthorized personnel by implementing the use of passwords that are for encryption keys and to make ease for the transmission confidential data via email platform.